Resilience of Biocontrol for Aflatoxin Minimization Strategies: Climate Change Abiotic Factors May Affect Control in Non-GM and GM-Maize Cultivars - Gasperini, Alessandra Marcon; Rodriguez-Sixtos, Alicia; Verheecke-Vaessen, Carol; Garcia-Cela, Esther; Medina, Angel; Magan, Naresh (Frontiers in Microbiology, 2019)
There has been significant interest in the development of formulations of non-toxigenic strains of Aspergillus flavus for control of toxigenic strains to reduce the aflatoxin B1 (AFB1) contamination of maize. In the future, climate change (CC) abiotic conditions of temperature (+2-4oC), CO2 (existing levels of 400 vs 800-1200 ppb) and drought stress will impact on the agronomy and control of pests and diseases. This study has examined (a) the effect of two-way interacting factors of water activity x temperature on colonisation and AFB1 contamination of maize cobs of different ripening ages, (b) effect of non-toxigenic strains of A. flavus on relative control of toxigenic A. flavus and AFB1 contamination of ripening cobs, (c) post-harvest control of AFB1 by non-toxigenic strains of A. flavus in non-GM and isogenic GM maize cultivars, and (d) impact of three-way interacting CC factors on relative control of AFB1 in maize cobs and in stored non-GM/GM cultivars. This has shown that colonisation and AFB1 production by a toxigenic A. flavus strain is conserved at 37oC when compared with 30oC, especially at the milk ripe (R3), dough (R4) and dent (R5) stages of cob development. However, pre-harvest biocontrol with a non-toxigenic strain was only effective at the R3 and R4 stages, not at the R5 stage. This was supported by relative expression of the aflR regulatory biosynthetic gene in the different treatments. Post-harvest storage of non-GM and GM cultivars showed that control was achievable at 30oC, with slightly better control in GM-cultivars in terms of the overall AFB1 concentration. When exposed to extreme three-way interacting CC factors pre-harvest ripened maize cobs (R5 stage), the non-toxigenic strain was not effective in controlling AFB1. However, in stored maize post-harvest, a non-toxigenic strains of A. flavus had conserved biocontrol of AFB1 contamination especially in the GM-maize cultivars. This was supported by the relative expression of the aflR gene in these treatments. This study suggests that the choice of the biocontrol strains must take into account their resilience to CC-related abiotic stress factors to ensure that control of AFB1 contamination can be conserved, both pre- and post-harvest.